2021
DOI: 10.1108/pm-01-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

CEO behavior and sustainability performance: the moderating role of corporate governance

Abstract: PurposeThis paper explores how the tension between a firm's CEO overconfidence feature and externally observable hubris attribute may determine the level of corporate sustainability performance. This work also contemplates the impact of the moderator “corporate governance practices.”Design/methodology/approachThis study uses a sample of 658 firm-year-observations using a sample of European real estate firms indexed on Stoxx Europe 600 Index from 2006 to 2019. To test the developed hypotheses, feasible generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…This concept represents an organization's ability to efficiently utilize its finite resources over time, reduce waste, and implement best practices (Aksoy et al, 2020). Corporate sustainability is assessed and quantified through three dimensions: economic, environmental, and social performance (Kouaib et al, 2021;Shad et al, 2019;Tze San et al, 2022). A study by Mousa et al (2022) found that organizations with superior sustainable performance are more likely to be able to lessen the negative effects of crises, like the current pandemic.…”
Section: Definition Of Risk Managementmentioning
confidence: 99%
“…This concept represents an organization's ability to efficiently utilize its finite resources over time, reduce waste, and implement best practices (Aksoy et al, 2020). Corporate sustainability is assessed and quantified through three dimensions: economic, environmental, and social performance (Kouaib et al, 2021;Shad et al, 2019;Tze San et al, 2022). A study by Mousa et al (2022) found that organizations with superior sustainable performance are more likely to be able to lessen the negative effects of crises, like the current pandemic.…”
Section: Definition Of Risk Managementmentioning
confidence: 99%
“…This approach claims that the decision to invest in environmental, social and governance activities is viewed as the manifestation of the managerial agency issues in the firms (Castillo-Merino & Rodríguez-Pérez, 2021;Ferrell et al, 2016). On the contrary, in the modern business upholding the sustainable concept, managers are demanded not only to maximize the wealth of the stakeholders through the economic aspect but also to resolve the social and environmental issues (So et al, 2021;Masud et al, 2018;Kouaib et al, 2021;Farooq et al, 2021;Kend, 2015). In the Indonesian context, the government started to regulate the implementation of social and environmental responsibilities through the Laws on Limited Companies in 2007 (Tjahjadi et al, 2021).…”
Section: Agency Theory Corporate Governance Sustainabilitymentioning
confidence: 99%
“…A powerful CEO could enhance a company's disclosure on social and environmental contexts (Gerged, 2021). Various researchers have attested that the CEO has a significant role in the explanation of socially responsible and sustainable activities (Cho et al, 2019;Kouaib et al, 2021). Thus, companies with good corporate governance practices will be more environmentally responsible.…”
Section: Corporate Governance and Sustainability Performancementioning
confidence: 99%